Permanência discente em cursos de pedagogia a distância : um estudo a partir da universidade aberta do Brasil - Soso, Felipe Sereno (2021)
The popularization of digital technologies has brought about profound changes in society. The new forms of interaction and communication mediated by non-physical spaces have enabled the expansion of Distance Education (DE). This type of education is growing rapidly in Brazil, and now comprises more than a quarter of all enrollments in undergraduate courses (INEP, 2020a). However, the high dropout rates put pressure on Higher Education Institutions (HEI) to define strategies to promote the permanence of their students until graduation. In this sense, this research was structured from the need to look at the management of institutions and evaluate how they are committed to the permanence of students in the modality. This research aims to identify and analyze how the Higher Education Institutions linked to the Open University of Brazil (UAB) promote the permanence of students in teacher training courses. For this, eight semi-structured interviews were conducted with coordinators of six different HEIs, and analysis of institutional documents. The understanding of the managers’ statements and the document analysis emphasized that the institutions have different levels of commitment to the institutionalization of the modality, which reflects directly on their performance to mitigate the dropout of students. Based on the identification of weaknesses in the courses, as well as good practices referred to in the literature, guidelines were presented that aim to promote the permanence of students in the contexts investigated. Keywords: Student permanence, Pedagogy, Distance Education, Open University of Brazil.